High‐titer post‐vaccine COVID‐19 convalescent plasma for immunocompromised patients during the first omicron surge. Issue 2 (16th March 2023) - Tayyar, Ralph; Wong, Lisa Kanata; Dahlen, Alex; Shu, Elaine; Pandey, Suchitra; Liu, Anne Y.
Abstract: Background: Transplant and hematologic malignancy patients have high Coronavirus disease 2019 (COVID‐19) mortality and impaired vaccination responses. Omicron variant evades several monoclonal antibodies previously used in immunocompromised patients. Polyclonal COVID‐19 convalescent plasma (CCP) may provide broader neutralizing capacity against new variants at high titers. Vaccination increases severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) titer in convalescent donors. Methods: We conducted a retrospective chart review of hospitalized immunocompromised patients with COVID‐19 who received high‐titer CCP during the first omicron surge, collected from vaccinated donors within 6 months of pre‐omicron COVID‐19. Data on safety and outcomes were extracted. Results: A total of 44 immunocompromised patients were included, 59.1% with solid organ transplant, 22.7% with hematopoietic cell transplant, 11.4% with hematologic malignancy, and 6.8% with autoimmune disease. Overall, 95% of CCP units transfused were from recently recovered and vaccinated donors and had SARS‐CoV‐2 antibody results 8‐ to 37‐fold higher than the Food and Drug Administration's cutoff for high‐titer CCP. There were two mild transfusion reactions. A total of 30‐day mortality was 4.5%. There were no differences in 100‐day mortality by underlying diagnosis, levels of immunosuppression, and timing of CCP administration. Patients with higher immunosuppression had significantly higher mean World Health Organization clinical progression scores at 30‐day post‐CCP compared to those with lower immunosuppression. Conclusions: CCP is a safe, globally available treatment for immunocompromised patients with COVID‐19. Mortality was lower in our cohort than that of COVID‐19 patients with similar immunocompromising conditions. Post‐vaccine CCP with very high titers should be prioritized for study in immunocompromised patients. Post‐vaccine CCP has the potential to keep pace with new variants by overcoming mutations at sufficiently high titer. Abstract : During the first omicron wave, high‐titer post‐vaccine COVID‐19 convalescent plasma was safe when given to 44 immunocompromised hospitalized patients with COVID‐19. Thirty‐day mortality was 4.5%. Later, administration more than 10 days from symptom onset was not associated with worse outcomes.